Effects of saline-alkali stress on cotton growth and physiochemical expression with cascading effects on aphid abundance - Gao, Yu; Liu, Bing; Wei, Hongyi; Lu, Yanhui (Frontiers in Plant Science, 2024)
Introduction Environmental stresses, such as soil salinity or alkalinity, usually affect crop growth and secondary plant metabolism, with follow on effects on foliar-feeding insects. Nevertheless, the underlying mechanism of how saline-alkali stress affects the key cotton pest Aphis gossypii Glover is poorly understood. Methods In this study, we first considered effects of three types of saline-alkali stress (i.e., salinity alone, alkalinity alone – both at different concentration – and their mixed effects) on cotton plants. We then measured impacts of stress on (1) above and below plant growth traits (e.g., plant height, leaf area, root volume), (2) levels of nutrients and secondary metabolites in cotton leaves, and (3) feeding behavior, life-table parameters, and population growth of A. gossypii. We then used a path analysis to evaluate cascading effects of changes in plant growth (due to stress) and changes in levels of nutrients or secondary metabolites on growth of individual cotton aphids and aphid populations. Results We found either salinity or alkalinity stresses significantly reduced cotton growth, increased the content of tannin, soluble sugars, and proline in the leaves, and suppressed aphid growth and development, (including longevity, fecundity, and intrinsic rate of increase) and aphid population growth. Alkalinity had stronger effects on these traits than did salinity. Discussion This work provides insights into the bottom-up interaction mechanism by which these environmental stresses mediate aphid infestation levels in the cotton agricultural ecosystem.